RNA editing by ADAR1 prevents MDA5 sensing of endogenous dsRNA as nonself - Liddicoat, Brian; Piskol, Robert; Chalk, Alistair M.; Ramaswami, Gokul; Higuchi, Miyoko; Hartner, Jochen C.; Li, Jin Billy; Seeburg, Peter H.; Walkley, Carl R. (Science, 2015)
RNA editing helps identify cellular RNAs - Adenosine bases in messenger RNA (mRNAs) can be enzymatically modified and changed into inosine bases. This RNA “editing” is mediated by adenosine deaminase acting on RNA (ADAR) enzymes. Liddicoat et al. show that the in vivo targets of the principal editing enzyme, ADAR1, are long double-stranded RNA (dsRNA) structures in noncoding portions of cellular mRNAs. ADAR1-directed editing of these cellular targets is critical to avoid activation of an immune response to dsRNA in the cytoplasm, because dsRNA is also a marker of viral infection. - Science, this issue p. 1115 - Adenosine-to-inosine (A-to-I) editing is a highly prevalent posttranscriptional modification of RNA, mediated by ADAR (adenosine deaminase acting on RNA) enzymes. In addition to RNA editing, additional functions have been proposed for ADAR1. To determine the specific role of RNA editing by ADAR1, we generated mice with an editing-deficient knock-in mutation (Adar1E861A, where E861A denotes Glu861→Ala861). Adar1E861A/E861A embryos died at ~E13.5 (embryonic day 13.5), with activated interferon and double-stranded RNA (dsRNA)-sensing pathways. Genome-wide analysis of the in vivo substrates of ADAR1 identified clustered hyperediting within long dsRNA stem loops within 3′ untranslated regions of endogenous transcripts. Finally, embryonic death and phenotypes of Adar1E861A/E861A were rescued by concurrent deletion of the cytosolic sensor of dsRNA, MDA5. A-to-I editing of endogenous dsRNA is the essential function of ADAR1, preventing the activation of the cytosolic dsRNA response by endogenous transcripts. - The principal RNA-editing enzyme modifies cellular RNAs to prevent their erroneous identification as foreign RNA. - The principal RNA-editing enzyme modifies cellular RNAs to prevent their erroneous identification as foreign RNA.
Gesehen am 22.06.2020